Academic achievement of elementary school-aged children with pre-anemic iron-deficiency - Paul Wiratama Pardede; Endang Windiastuti; Bambang Tridjaja (Paediatrica Indonesiana, 2009)
Background Relationship between iron deficiency andcognitive function has been investigated in many studies, butthey usually focused on iron deficiency anemia. Brain ironstorage might have already decreased before anemia exist.Objectives To investigate the prevalence of pre-anemic irondeficiencyin school-aged children and to determine whetherthis condition is a risk factor for low academic achievement.Methods A cross-sectional study was conducted on 87 subjectsof znd,6th grade in SDN 04 Petang, Kramat, Senen, Jakartaon August 2008. The subjects underwent peripheral bloodand ferritin serum concentration examinations. Twentyninesubjects who suffered from anemia were excluded. Theremaining 58 subjects were classified into normal body ironstatus group and preanemic iron-deficiency group.Results The prevalence of pre-anemic iron-deficiency in SDN04 Petang, Kramat was 6%. The prevalence ratio to determinewhether pre-anemic iron-deficiency was a risk factor for lowacademic achievement could not be calculated because theminimal sample number required was not reached. There wasno relationship between pre-anemic iron-deficiency and lowacademic achievement for mathematics, Indonesian language,science, and social science.Conclusions The prevalence of pre-anemic iron-deficiency inSDN 04 Petang, Kramat Senen Jakarta was 6%. This studyis not able to determine whether pre-anemic iron-deficiencyis a risk factor for low academic achievement in school-agedchildren; therefore further study with more efforts to detectthe presence of iron deficiency in children with inflammationis needed.